Online Learning: Signal Integration and Augmented Reality Helping Children with Down Syndrome - Nor Azril Mohd Ghazali; Che Zalina Zulkifli; Mohd Zahuri Khairani; Mohd Fauzi Sedon; Joko Suyono; Yohanes Sugiyanta (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This study focuses on how online learning can aid in the development of the Augmented Reality (AR) technology, "Mar-Care”, which possesses features that will attract elementary students to learn Makaton. Makaton is a Sign Language whose inception dates back to around 1972/73 and it was meant to be used by people with learning disabilities to help develop language and communication skills. This study online learning involves AR technology and the use of Padlet as e-learning platforms a forum for students to discuss and express their opinions. Design: The methods used throughout the production of Mar-Care application technology education learning online tools are the Padlet platform. Findings: Visual representation of the basic hand gestures through 3D animation is shown on the Padlet to explain online learning Research limitations: This study has developed an online medium for online learning. Practical implications: A large number of software used to produce online learning tools successfully make the discussion space between students and teachers. Paper type: Research Paper